The White Indians of Mexican Cinema : Racial Masquerade throughout the Golden Age - García Blizzard, Mónica (Book collections on Project MUSE., 2022)
"Examines the filmic representation of Whiteness as Indigeneity and its role in mediating racial politics in Mexico"--